Development of STEAM-Based Electronic Practicum Module on the Topic of Saponification - Handayani, Dewi; Agustiningtias, Wardah Izzati; Nurhamidah, Nurhamidah; Andriani, Yosie (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2025)
The integration of STEAM (Science, Technology, Engineering, Arts, and Mathematics) approaches in chemistry education offers new opportunities to foster active, interdisciplinary, and skills-oriented learning. However, practical resources that align with this pedagogical framework, particularly in laboratory instruction, remain limited. This study aims to develop and evaluate a STEAM-based electronic practicum guide on the topic of saponification, focusing on its feasibility, student responses, and its effectiveness in enhancing students' psychomotor skills. The development process followed the 4D model (Define, Design, Develop, and Disseminate), with implementation limited to the development stage. Participants included fourth-semester chemistry education students. The practicum guide underwent expert validation and was trialed through student feedback and performance-based observation of psychomotor competencies. The results revealed that the practicum guide achieved a high validity score (87.8%), received very positive student responses (93.1%), and significantly supported the development of psychomotor skills, with an average performance score of 94.2%. These findings suggest that the STEAM-based practicum guide is both feasible and effective as an instructional tool, offering meaningful and engaging learning experiences in chemistry laboratories. The study contributes to the advancement of innovative practicum materials and supports the implementation of STEAM principles in science education.